The Role of Social Media in Stunting Prevention Education among Mothers of Toddlers: A Narrative Review - Honesty Pujiyani; Nindi Pramesthi V. Putri; Nadia D. Rosanti; Renidya Asyura M.D. Fa’ni; Fatihah Wari Nurjanah (Jurnal Ragam Pengabdian, 2026)
Stunting continues to be a significant public health concern across many developing nations, including Indonesia, and is closely associated with inadequate maternal knowledge and suboptimal infant feeding practices. The rapid expansion of digital technology has created opportunities to utilize social media as a medium for health education. This study aimed to narratively review the utilization of social media as an educational instrument for stunting prevention. A narrative review design was applied by searching articles in Science Direct and PubMed published between 2020 and 2025. Eligible studies were primary research articles in English or Indonesian that examined social media–based education related to stunting among mothers, adolescent girls, parents, or the community. The selected studies were analysed descriptively and synthesized narratively. The findings showed that most studies employed quasi-experimental and pretest–posttest designs. WhatsApp was the most frequently used platform, followed by other social media, Instagram and TikTok. Overall, social media based interventions consistently improved knowledge, in several studies, also enhanced attitudes and preventive practices related to stunting. Messaging platforms were particularly useful for sustained education, while short video platforms demonstrated strong potential for increasing engagement among younger audiences. Supporting factors included high accessibility, time flexibility, and attractive visual content, whereas barriers involved variations in digital literacy, limited internet access, and heterogeneity of study designs. In conclusion, social media is promising and effective for stunting prevention education and should be integrated into maternal and child health programs to strengthen the reach and continuity of nutrition education.